First - principles calculations on stability and mechanical properties of various ABO3 and their alloys - Akgenc, B.; Kinaci, A.; Tasseven, C.; Cagin, T. (ELSEVIER SCIENCE SA, 2018)
In this study, we perform first principle calculations based on density functional theory (DFT) to obtain the ground state structural, elastic and dielectric properties of various ABO(3) type ceramics and their {A(x)A'((1-x))}BO3 and A(BxB'((1-x))}O-3 alloys. To represent alloy perovskites, we employ supercells with species A, A' = Ba, Sr, Pb; B, B' = Ti, Zr. The effects of composition and atomic configuration/order on lattice structure, thermodynamics, elastic constants and dielectric properties are evaluated. In calculations, we have used linear response and homogeneous field methods and we have also provided an assessment of the performance of these approaches in the determination of aforementioned properties. We have computed dielectric and piezoelectric properties for the cubic form of alloy perovsldtes. Even though cubic form of alloy perovskites does not have any piezoelectric properties, owing to crystallo-graphic site occupied by different type of atoms, the inversion symmetry breaks down and the structures develop a small tetragonality, in turn a small polarization and non-zero but quite small piezoelectric coefficients emerge as expected. For instance the observed maximum piezoelectric constant for BaZr(1-x)TixO3 is 0.554x10(-15)C/N. The magnitudes are smaller than the feasible ranges for actual application needs, but they may increase substantially upon phase to lower symmetry tetragonal forms transformation. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: Piezoelectric ceramics; ABO3 type perovskites; Mechanical properties; Structural properties; Piezoelectric properties; Density functional theory; X-RAY; ELASTIC PROPERTIES; PHASE-TRANSITIONS; SRTIO3; BATIO3; PBTIO3; POLARIZATION; CRYSTALS; BAZRO3; AGNBO3; Materials Science